2019
DOI: 10.1108/heswbl-07-2018-0072
|View full text |Cite
|
Sign up to set email alerts
|

Improving the soft skills of engineering undergraduates in Malaysia through problem-based approaches and e-learning applications

Abstract: Purpose Various studies around the globe indicate lack of soft skills in engineering students, graduating from universities, although the bulk of studies in various disciplines indicate an improvement in various skills through implementation of a problem-based learning (PBL) approach. The purpose of this paper is therefore to identify and determine the effects of PBL in improving and developing soft skills, conflict resolution traits and aspects of enhancing group learning in undergraduates. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 18 publications
3
39
0
2
Order By: Relevance
“…The questionnaires were distributed randomly to students without choosing a gender [19]. After that, they need to answer the other similar instruments from previous regarding the video they watch.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires were distributed randomly to students without choosing a gender [19]. After that, they need to answer the other similar instruments from previous regarding the video they watch.…”
Section: Methodsmentioning
confidence: 99%
“…In this qualitative research is an approach for exploring and understanding the meaning individuals or group describe to a social or human problem (Creswell, J.,W., 2013). This research location at Pancasila and Civic Education Study Program, Faculty of Social Sciences, Universitas Negeri Jakarta.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study (Deep et al, 2019) was conducted to identify and determine the effects of PBL in improving and developing soft skills among undergraduates has revealed that PBL has a significant effect on improving students' soft skills and enhancing group learning, including overcoming communication conflicts.…”
Section: Pbl In Software Engineering Educationmentioning
confidence: 99%
“…PBL is an approach for reducing the gap between theory and practice when it is based on real problems, and it is able to provide students with the chance to propose the solution strategy that contributes to understanding the real-life problem and solution (Corrêa and Martins, 2016). In addition, PBL also allows the students to develop soft skills such as teamwork, self-assessment, problem-solving, leadership, and negotiation (Deep et al, 2019;Jabarullah and Hussain, 2019). This study aims to investigate the implementation of a software engineering course at the Faculty of Computer Science and Engineering, the University of Jeddah, using PBL methodology from the students' perspective in the learning process.…”
Section: Introductionmentioning
confidence: 99%